Journal of Engineering Physics and Thermophysics - Penyazkov, Oleg G.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Engineering Physics and Thermophysics publishes the results of theoretical and experimental studies in the following fields: Thermophysics; Heat and mass transfer; Theory of heat conduction; Thermodynamics of irreversible processes; Theory of drying; Heat and mass transfer in disperse and porous systems; Rheodynamics; Rheology. The main focus of this publication is to highlight papers detailing with important, modern day problems, which challenge Scientists in the fields of Technology, Engineering and Physics. Journal of Engineering Physics and Thermophysics is an English translation of the Russian language journal Inzhenerno-fizicheskii Zhurnal, a publication of the Academy of Sciences of Belarus. The English edition has been published since the very first volume of the Russian journal appeared in 1965. Both editions are published bimonthly. As the entire content is available in both Russian and English, this valuable resource can reach a global audience, thus facilitating international communication between researchers involved in similar studies across the world, this is further facilitated by the online availability of the journal through www.SpringerLink.com. The Russian Volume Year is published in English from April. All articles are peer-reviewed.
Keywords: Chemical engineering; Mechanics; Thermodynamics; Statistical physics; Dynamical systems; Heat engineering; Heat transfer; Mass transfer; Engineering Thermodynamics, Heat and Mass Transfer; Thermodynamics; Industrial Chemistry/Chemical Engineering; Complex Systems; Classical Mechanics